2021
DOI: 10.5468/ogs.21093
|View full text |Cite
|
Sign up to set email alerts
|

Hyperthermic intraperitoneal chemotherapy as consolidation treatment of advanced stage ovarian cancer

Abstract: To investigate the therapeutic efficacy of hyperthermic intraperitoneal chemotherapy (HIPEC) as consolidation treatment after completing first-line treatment in patients with advanced ovarian cancer. MethodsA retrospective chart review was conducted on patients treated at the Comprehensive Gynecologic Cancer Center between January 2014 and 2019. Based on the inclusion criteria, 24 eligible patients who received HIPEC (paclitaxel 175 mg/m 2 , for 90 min, at 42°C) (HIPEC group) as consolidation treatment after t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
(30 reference statements)
0
2
0
Order By: Relevance
“…One retrospective study ( 21 ) conducted by Ziying Lei et al showed that primary cytoreductive surgery with HIPEC was associated with better long-term survival. A retrospective study ( 22 ) conducted by Jieun Ko et al demonstrated that consolidation HIPEC has no specific survival benefit for patients with advanced ovarian cancer after completion of first-line treatment. A study ( 23 ) conducted by Jessica Jou et al resulted in an unexpected conclusion; the study revealed that HIPEC was associated with an increased risk for platinum-refractory or resistant disease in ovarian cancer patients who underwent NACT and IDS, while no benefit was shown in median PFS.…”
Section: Discussionmentioning
confidence: 99%
“…One retrospective study ( 21 ) conducted by Ziying Lei et al showed that primary cytoreductive surgery with HIPEC was associated with better long-term survival. A retrospective study ( 22 ) conducted by Jieun Ko et al demonstrated that consolidation HIPEC has no specific survival benefit for patients with advanced ovarian cancer after completion of first-line treatment. A study ( 23 ) conducted by Jessica Jou et al resulted in an unexpected conclusion; the study revealed that HIPEC was associated with an increased risk for platinum-refractory or resistant disease in ovarian cancer patients who underwent NACT and IDS, while no benefit was shown in median PFS.…”
Section: Discussionmentioning
confidence: 99%
“…We read with great interest the study entitled “Hyperthermic intraperitoneal chemotherapy as consolidation treatment of advanced-stage ovarian cancer”- a retrospective chart review by Ko et al [ 1 ]. We appreciate the authors for conducting the trial on this promising futuristic aspect of HIPEC.…”
mentioning
confidence: 99%